Pathophysiological and molecular considerations of viral and bacterial infections during maternal-fetal and –neonatal interactions of SARS-CoV-2, Zika, and Mycoplasma infectious diseases - Ferreira, Gonzalo; Blasina, Fernanda; Rodríguez Rey, Marianela; Anesetti, Gabriel; Sapiro, Rosana; Chavarría, Luisina; Cardozo, Romina; Rey, Grazzia; Sobrevia, Luis [UNESP]; Nicolson, Garth L. (Elsevier, 2022)
During pregnancy, a series of physiological changes are determined at the molecular, cellular and macroscopic level that make the mother and fetus more susceptible to certain viral and bacterial infections, especially the infections in this and the companion review. Particular situations increase susceptibility to infection in neonates. The enhanced susceptibility to certain infections increases the risk of developing particular diseases that can progress to become morbidly severe. For example, during the current pandemic caused by the SARS-CoV-2 virus, epidemiological studies have established that pregnant women with COVID-19 disease are more likely to be hospitalized. However, the risk for intensive care unit admission and mechanical ventilation is not increased compared with nonpregnant women. Although much remains unknown with this particular infection, the elevated risk of progression during pregnancy towards more severe manifestations of COVID-19 disease is not associated with an increased risk of death. In addition, the epidemiological data available in neonates suggest that their risk of acquiring COVID-19 is low compared with infants (<12 months of age). However, they might be at higher risk for progression to severe COVID-19 disease compared with older children. The data on clinical presentation and disease severity among neonates are limited and based on case reports and small case series. It is well documented the importance of the Zika virus infection as the main cause of several congenital anomalies and birth defects such as microcephaly, and also adverse pregnancy outcomes. Mycoplasma infections also increase adverse pregnancy outcomes. This review will focus on the molecular, pathophysiological and biophysical characteristics of the mother/placental-fetal/neonatal interactions and the possible mechanisms of these pathogens (SARS-CoV-2, ZIKV, and Mycoplasmas) for promoting disease at this level.
Keywords: Bacteria; Maternal-fetal interphase; Mycoplasma; Neonates; Pregnancy; Viruses